Arising reading patterns in understanding literary texts - Revathi Gopal; Charanjit Kaur Swaran Singh (Universitas Syiah Kuala, 2020)
This paper reviews reading attempts made by students at the lower secondary – level in oral reading and retelling to understand literary texts. The study involved a qualitative research method in collecting data, which relates to the students’ reading patterns in understanding literary texts and the impact of students’ reading patterns on literary texts comprehension. The sample in this study comprised six average ability Form One (i.e. seventh grade) students from a secondary school. Data collection techniques included content analysis of students’ oral reading and retelling. Students’ oral reading and retelling were centred in the literature textbook currently used in lower secondary school. Data collected were subsequently analysed by using frequency counts in the form of percentages. The findings from oral readings show that students formed their own mental framework to guide them through in text comprehension, and the results of retellings analysis suggest that the literary texts were readable and were within the students’ comprehension level. However, none was able to infer beyond the text and to relate the text to one’s own life. This did not influence students’ text comprehension. The study indicates that different forms of patterns arose during oral reading among students in ways how they connected the ideas on the page to comprehend the literary texts. This aided teachers in their choices of classroom instructions that best fit the students’ reading ability.